Inhaled powder compared with aerosol administration of fenoterol in asthmatic children. Issue 1 (January 1980) - Chambers, S; Dunbar, J; Taylor, B
Abstract : Fenoterol as a powdered inhalation was shown to have a longer and stronger bronchodilator effect than the same dose inhaled from a standard metered dose aerosol in a double-blind double-placebo controlled cross-over study in 13 severely asthmatic children. The powder method of administration is free from many of the disadvantages of pressurised aerosols and may prove the method of choice in childhood.